FACTORS THAT INFLUENCE STUDENTS’ AWARENESS IN PARTICIPATING OF CASH WAQF - Raden Muh. Syakur Fathurrahman; Hartomi Maulana (Islamic Business and Management Journal, 2018)
Currently, cash waqf is considered as an important role in developing waqf institutions and increase the social economic of society. However, the literature related to a social psychological understanding of the factors that highlight a person's decision to give cash waqf has been very few. Hence, this study attempts to examine factors that influence waqif intention to participate in contributing cash waqf in the context of muslim Indonesia particularly amongst students at the University of Darussalam Gontor (UNIDA Gontor) Ponorogo. For this purpose, a theory of reasoned action (TRA) used as a research framework. Quantitative approach with constructing a questionnaire employed to measure student giving intention behavior. The study revealed that student’s attitude and subjective norms are found to have a significant impact on their intention to participate in cash waqf contribution. This study may be pioneering in understanding the factors contributing the receptivity of cash waqf in Indonesia. Additionally, the study validates the applicability of the theory of reasoned action in the context of cash waqf.